Corrosion resistance evaluation of carbon steel plates protected by zirconium and titanium nanoceramic coatings (Research, Society and Development, 2020)
Metal surface pre-treatment is a known process and is used to increase corrosion performance as well as improve adhesion between the substrate and the paint layer. The present paper evaluated the corrosion resistance of carbon steel before and after treatment with nanoceramic coatings. The comparison was between a pure zirconia nanoceramic compound (Bonderite NT-1), with the addition of a dispersant (polyacrylic acid) and another nanoceramic coating developed from titanium oxide. Additionally, salt spray, open circuit potential (OCP), polarization and impedance tests were performed to obtain a methodology to quantitatively assess the quality of protection. The zirconia coating presented superior characteristics than the corrosion protection. The corrosion potential of this coating was about twice as low as the others. The addition of dispersant produced no significant improvements in corrosion resistance and was similar to uncoated carbon steel, possibly due to the high concentration used.